2007
DOI: 10.1210/jc.2007-0445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cortisol on Carbohydrate, Lipid, and Protein Metabolism: Studies of Acute Cortisol Withdrawal in Adrenocortical Failure

Abstract: Context:Cortisol is an important catabolic hormone, but little is known about the metabolic effects of acute cortisol deficiency.Objective: The objective of the study was to test whether clinical symptoms of weight loss, fatigue, and hypoglycemia could be explained by altered energy expenditure, protein metabolism, and insulin sensitivity during cortisol withdrawal in adrenocortical failure.Design, Participants, and Intervention: We studied seven women after 24-h cortisol withdrawal and during replacement cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 35 publications
3
95
2
1
Order By: Relevance
“…The study by Christiansen et al demonstrated that acute withdrawal of cortisol increased insulin sensitivity close to 70%, increased glucose oxidation by 50%, with decreased endogenous glucose production, implying that adrenocortical failure could result in hypoglycemia (111). Meyer et al studied 13 patients with primary adrenal insufficiency using continuous glucose monitoring for 3-5 days (112).…”
Section: Hypoglycemia In Adrenal Insufficiencymentioning
confidence: 99%
“…The study by Christiansen et al demonstrated that acute withdrawal of cortisol increased insulin sensitivity close to 70%, increased glucose oxidation by 50%, with decreased endogenous glucose production, implying that adrenocortical failure could result in hypoglycemia (111). Meyer et al studied 13 patients with primary adrenal insufficiency using continuous glucose monitoring for 3-5 days (112).…”
Section: Hypoglycemia In Adrenal Insufficiencymentioning
confidence: 99%
“…*In AI, insulin sensitivity is enhanced because of cortisol deficiency [11], and an excessive hypoglycemic reaction is often introduced by ITT. Usually, intravenous injection of rapid-acting insulin at a dose of 0.1 U/kg body weight (BW) is recommended.…”
Section: I-26mentioning
confidence: 99%
“…In contrast to the anabolic properties of DHEA and DHEAS, cortisol (when in excess) has catabolic properties [138]. Cortisol mobilises glucose, free fatty acids and amino acids from endogenous stores [138].…”
Section: Copd and Adrenal Axismentioning
confidence: 99%